Preserving Heritage: The Tradition of Manakib Recitation among Banjar Women - Alfisyah, Alfisyah; Komalasari, Kokom; Subiyakto, Bambang; Mulyana, Agus (KARSA Journal of Social and Islamic Culture, 2025)
This paper examines local culture and traditions as representations or means of accommodation for the socio-economic and cultural expectations of the Banjar community, particularly among women. Specifically, this paper explores how the Banjar community, especially Banjar women, build, grow, and transform knowledge through the reading of Siti Khadijah’s manaqib. The recitation of Siti Khadijah’s manaqib is a tradition among Banjar women, and it is performed on various occasions during specific religious rituals. In particular, the recitation of Siti Khadijah’s manaqib is also routinely carried out in religious institutions on the 11th day of each Hijri month. Banjar women in this study play an active role in socio-cultural transformation. An important finding in this study is that religious institutions, especially the ritual of reading Siti Khadijah’s manaqib, are a dynamic expression of Banjar women’s social and economic spirit. Through religious institutions, primarily through the ritual of reading Siti Khadijah’s manaqib, women play a role in dynamizing the economy and teaching worldly asceticism. Siti Khadijah’s reading of manaqib reflects how local communities foster and raise hopes for prosperity, ensuring the sustainability of life and society.